Effect of carbon content on the Curie temperature of WC-NiFe cemented carbides. (January 2019) - Hou, Ziyong; Linder, David; Hedström, Peter; Borgenstam, Annika; Holmström, Erik; Ström, Valter
Abstract: We have investigated the effect of the carbon content on the Curie temperature of a cemented carbide composite material with a Ni-Fe alloy as the binder phase and WC as the hard phase. In the carbon concentration range from 5.72 to 5.83 wt% carbon, which covers the interval where WC coexists with fcc Ni-Fe without other phases (the 'carbon window'), the Curie temperature rises from 200 to 527 °C. This result indicates the possibility to use the Curie temperature to determine the carbon balance in the system. With thermodynamic calculations and kinetic simulations we can quantitatively establish the correlation between the carbon and tungsten content of the binder phase and the Curie temperature. This strong compositional effect on the Curie temperature is quantitatively very different from the conventional Co-based cemented carbides, with Curie temperatures of about 950–1050 °C. Graphical abstract: Relative loss of magnetization versus temperature for five WC-NiFe composites with varying carbon content. The carbon content from 5.72 to 5.83 wt% C increases the Curie temperature from 200 °C to 527 °C. This strong dependence on the carbon content can replace much more elaborate methods for quality control of environmentally benign hard metal composites. Highlights: Quality control of Hard Metal composites means control of the 'carbon window' Saturation magnetization works for Co binder with tungsten carbide Curie point can work for Ni-Fe binders Accurate determination of the carbon and tungsten concentration Handles non-equilibrium solidification with thermodynamical calculations